2011
DOI: 10.1039/c1cp20749k
|View full text |Cite
|
Sign up to set email alerts
|

Polyelectrolyte adsorption onto oppositely charged interfaces: unified approach for plane, cylinder, and sphere

Abstract: A universal description is presented for weak adsorption of flexible polyelectrolyte chains onto oppositely charged planar and curved surfaces. It is based on the WKB (Wentzel-Kramers-Brillouin) quantum mechanical method for the Green function equation in the ground state dominance limit. The approach provides a unified picture for the scaling behavior of the critical characteristics of polyelectrolyte adsorption and the thickness of the adsorbed polymer layer formed adjacent to the interface. We find, particu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

13
113
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(127 citation statements)
references
References 77 publications
(100 reference statements)
13
113
1
Order By: Relevance
“…[12][13][14][15][16][17][18][19][20][21][22][23][24][25] An important aspect of PE adsorption is the charge inversion, that is, the total amount of charges on adsorbed PE chains overcompensates that of the surface charges of the object. Other interesting issues regarding the PE adsorption, such as the critical condition for the adsorption, the thickness of the polymer layer, the addition of the salt ions, and the difference between planar and curved (cylindrical, spherical) charged objects, have also attracted the research attention.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…[12][13][14][15][16][17][18][19][20][21][22][23][24][25] An important aspect of PE adsorption is the charge inversion, that is, the total amount of charges on adsorbed PE chains overcompensates that of the surface charges of the object. Other interesting issues regarding the PE adsorption, such as the critical condition for the adsorption, the thickness of the polymer layer, the addition of the salt ions, and the difference between planar and curved (cylindrical, spherical) charged objects, have also attracted the research attention.…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown by the scaling law, analytical and computational studies that, the thickness of the adsorbed polymer layer scales with both the linear charge density or average charge fraction of PE chains and the surface charge density as a power law, with the scaling exponent of about −1/3. 20,[22][23][24][25]51 Another interesting finding is that, at relatively low ionic strength, a curved convex surface entails a much higher surface charge density to trigger the PE adsorption than does a planar surface. [22][23][24] The adsorption of PEs with an annealed charge distribution on oppositely charged surfaces has been studied to a less extent compared to PEs with a smeared charge distribution.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Without external forces and melting, the electrostatically driven adsorption-desorption transition of unconstrained polyelectrolyte chains such as DNA onto oppositely charged curved surfaces has been examined in detail theoretically [51,52] and by computer simulations [53]. The scaling laws for the critical adsorption transition were obtained experimentally as functions of polyelectrolyte chain-surface adhesion strength, salt conditions, surface curvature, and chain stiffness [54].…”
Section: Modeling Virus-induced Dna Melting and Tension Formationmentioning
confidence: 99%
“…Recent analytical studies [35,[46][47][48][49][50][51][52][53][54][55][56][57][58][59][60][61][62] and numerical simulations [12,13,36,[63][64][65][66][67][68][69][70][71][72][73][74][75][76][77][78] have provided very useful insight into the essential role that electrostatic interactions play in determining the structural properties of charged polymer-sphere complexes. It was shown that a minimal chain-sphere model for nucleosome core particles [37][38][39][40][41]51] can closely predict the experimentally observed [79][80][81][82][83][84]…”
Section: Introductionmentioning
confidence: 99%